A SERVICE ORIENTED ARCHITECTURE FOR INTERNET OF THINGS (IOT) - Balasubramaniam, Sandhya; Sarala, V; Kavitha, J.C (IJRDO -Journal of Computer Science Engineering, 2015)
Internet of things (IoT) is changing the way we identify information. It has motivated solutions for anumber of everyday problems. With the advent of IoT, the internet will house several “intelligent “objectscapable of making their own decisions. The basic architecture of IoT is characterized by the presence of threedistinct layers, the sensing layer, the network layer and the application layer. The proposed paper aims atproviding an efficient platform to develop solutions for the IoT. Service oriented architecture (SOA) has seentremendous growth in the recent years. It has become one of the widely used platforms for development. In theproposed paper a SOA layer helps to manage the data and information. The heterogeneous nature of data in anIoT environment can be effectively handled with the help of a service framework.